An Analysis of Purchase Intentions for Cosmetic Products Using Tiktok Social Media Marketing - Wijaya, Acum; Rosadi, Rama (Universitas Indonesia Mandiri, 2025)
It is impossible to separate the several digital platforms utilized in business marketing from the current environment. Tiktok, a digital platform that lets users upload videos, is one social media site that is seeing a sharp increase in users. According to data from the website data.goodstats.id, 112 million Indonesians use the Tiktok social media platform, ranking it second globally after 116 million users in the US. However, as part of the company's product marketing plan, Tiktok has not been utilized to its full potential in Indonesia. In light of these circumstances, the purpose of this study was to investigate and determine how Tiktok social media affects interest in purchasing cosmetics. This study employed a quantitative approach using a survey methodology. In the meantime, 100 students from three universities in the Bekasi Regency were given questionnaires to complete in order to collect data. The examination of the processed data reveals that interest in purchasing cosmetic products is influenced by Tiktok social media marketing.